Institutional Dynamics of Halal Tourism Development in Indonesia and Malaysia - Musthofa, Budiman Mahmud; Pranita, Diaz; Rasul, Mohamad Sattar; Haidlir, Banu Muhammad (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2023)
In the context of Southeast Asia, Muslim-majority nations Indonesia and Malaysia had pioneered the development of halal tourism. Nevertheless, Malaysia has outperformed Indonesia in cultivating its halal tourism industry. The research sought to investigate the political economy factors contributing to this discrepancy. The research posited that the emergence of Islamic identity, the intensification of Islam’s politicization, and the varying degrees of capitalizing on Islamic values are three crucial determinants influencing the relative success of Malaysia’s halal tourism industry compared to Indonesia’s. Firstly, the perception of Islamic identity in Malaysia is less threatening compared to that in Indonesia. Secondly, the politicization of Islam is less pronounced in Malaysia than in Indonesia. To examine these assertions, the research utilized a methodological blend of primary and secondary data, incorporating interviews with policymakers and stakeholders of halal tourism in both countries. In addition to identifying the critical factors shaping the development of halal tourism, the research contributed by offering several recommendations concerning the innovative aspect of halal tourism branding. It was argued that within the growth of halal tourism in a nation, debates surrounding the emergence of Islamic identity in aspects of halal tourism can potentially obstruct the advancement of cultural tourism commodities. Consequently, the research enhances our understanding of the complex interplay between political economy factors and the evolution of halal tourism from an academic perspective.